2017
DOI: 10.28933/ijhp-2017-07-0901
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay guided fractionation-an emerging technique influence the isolation, identification and characterization of lead phytomolecules

Abstract: N e e l e s h M a l v i y a a n d S a p n a Malviya. Bioassay guided fractionation-an emerging technique influence the isolation, identification and characterization of lead phytomolecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…Natural products have received great prominence in recent years due to the promising anti‐inflammatory and immunomodulating activity of extracts from plants and marine organisms and their isolated compounds . Some of the leading pharmaceutical and research institutions have demonstrated growing interest in investigating plants to discover medically useful compounds . This study is part of an ongoing investigation on the chemical composition and immunomodulating properties of Brazilian green propolis (BGP) and its main botanical source, Baccharis dracunculifolia D.C. (Asteraceae) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Natural products have received great prominence in recent years due to the promising anti‐inflammatory and immunomodulating activity of extracts from plants and marine organisms and their isolated compounds . Some of the leading pharmaceutical and research institutions have demonstrated growing interest in investigating plants to discover medically useful compounds . This study is part of an ongoing investigation on the chemical composition and immunomodulating properties of Brazilian green propolis (BGP) and its main botanical source, Baccharis dracunculifolia D.C. (Asteraceae) …”
Section: Introductionmentioning
confidence: 99%
“…The selection of suitable extracts for the production of commercial products for a given therapeutic application requires not only the knowledge of the extracts’ chemical composition and chemical markers, but also the availability of bioassays to monitor their biological activity . In this sense, to develop BdE‐based anti‐inflammatory medicines, it is important to continue investigating how it modulates the effector functions of immune cells through different experimental approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the in vitro antifungal phenotypes observed were consistent; observed in independent isolates, across duplicate assays and under two different culture environment conditions. Thus, while beyond the scope of this study, the bioactive compounds should be discoverable using bioassay guided fractionation and isolation [ 70 , 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is to achieve a specific class of bioactive metabolites or, preferentially, a unique and well-defined bioactive molecule. This process is called bioassay-guided fractionation and is emerging in the field of drug discovery from natural sources [201]. This approach usually starts with different extracts obtained by using solvents with different polarities, in order to have a set of extracts enriched in different types of metabolites.…”
Section: Lipidomics For the Analysis Of Bioactive Lipids In Plants Anmentioning
confidence: 99%
“…The bioassay-fractionation-bioassay sequence can go around until a promising candidate molecule or family of molecules are considered and then it is characterized. The first step of fractionation is typically a liquid–liquid extraction (solvent–solvent partition), and normally uses chromatography techniques, as TLC and column chromatography [ 201 , 202 , 203 ]. Isolated fractions are assayed afterwards.…”
Section: Lipidomics For the Analysis Of Bioactive Lipids In Plantsmentioning
confidence: 99%